Measuring damages in the law of obligations : the search for harmonised principles - Harder, Sirko (Hart Pub., 2010)
This book challenges certain differences between contract, tort and equity in relation to the measure (in a broad sense) of damages. Damages are defined as the monetary award made by a court in consequence of a breach of contract, a tort or an equitable w.